The Correlation of Risk Factors to the incidence of Pediculosis capitis on Students in Pondok Pesantren Miftahul Ulum, Jember - Nihayah Lukman; Yunita Armiyanti; Dini Agustina (Journal of Agromedicine and Medical Sciences, 2018)
ABSTRACT Pediculosis capitis is a scalp disease caused by obligate ectoparasite (mite or lice) infection of Pediculus humanus var. capitis. This disease is a contagious disease that influenced by environment and behavior, so it becomes a dominant public health problem in densely populated environment like in boarding school. Some risk factors that cause Pediculosis capitis are; sex, educational level, hair wash frequency, use of comb or hair accessories together, use of bedding or bed together, hair length, and hair type. This study aims to determine the most dominant incidence, analyze the risk factors, and know the biggest risk factors to the incidence of Pediculosis capitis in santri at Pondok Pesantren Miftahul Ulum, Jember. The type of research that used was observational analytics with case control design conducted on 287 samples of SMP and SMA Miftahul Ulum students who fulfilled the inclusion and exclusion criterias. From this research, the proportion of Pediculosis capitis incidence was 214 respondents (74,6%), and then analyzed by Chi-Square test, it was found that the variables had significant relationship (p <0,05) to Pediculosis capitis occurrence, among others; sex, hair wash frequency, use of comb or hair accessories together, use of bedding or bed together, hair length and hair type. The result of logistic regression test shows that sex was the most biggest variable (p value = 0,000). Keywords: Pediculosis capitis, risk factors, boarding school